Pengaruh Pengasuhan Orang Tua Berpendidikan Rendah terhadap Perilaku Anak - Arifin, Maulana; Faisal, M.; Ayubi, Nuril (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2023)
The family is the first environment that a child encounters, with his father, mother and siblings. is a role model for their children. Children tend to imitate the behavior of the father, and the mother forbids the behavior of others. because mom and dad are the characters they meet the most. This is because the formation of personality in children is essentially based on the behavior of their parents. Parents who never pay attention to their children, freedom for children without proper supervision, lack of communication with children, and parents always fulfill all the wishes of children. Educational Model Such parents educate their children according to their wishes and take care of their family because children think that everything will go according to their wishes. Since there are no rules in the family, children can do whatever they want.